Effects of nonselective internal iliac artery angioembolization on pelvic venous flow in the swine model. Issue 2 (August 2021) - Sherman, Nathan C.; Williams, Keneeshia N.; Hennemeyer, Charles T.; Devis, Paola; Chehab, Mohamad; Joseph, Bellal; Tang, Andrew L.
Abstract : BACKGROUND: Pelvic angioembolization (AE) is a mainstay in the treatment algorithm for pelvic hemorrhage from pelvic fractures. Nonselective AE refers to embolization of the bilateral internal iliac arteries (IIAs) proximally rather than embolization of their tributaries distally. The aim of this study was to quantify the effect of nonselective pelvic AE on pelvic venous flow in a swine model. We hypothesized that internal iliac vein (IIV) flow following IIA AE is reduced by half. METHODS: Nine Yorkshire swine underwent nonselective right IIA gelfoam AE, followed by left. Pelvic arterial and venous diameter, velocity, and flow were recorded at baseline, after right IIA AE and after left IIA AE. Linear mixed-effect model and signed rank test were used to evaluate significant changes between the three time points. RESULTS: Eight swine (77.8 ± 7.1 kg) underwent successful nonselective IIA AE based on achieving arterial resistive index of 1.0. One case was aborted because of technical difficulties. Compared with baseline, right IIV flow rate dropped by 36% ± 29% ( p < 0.05) and 54% ± 29% ( p < 0.01) following right and left IIA AE, respectively. Right IIA AE had no initial effect on left IIV flow (0.37% ± 99%, p = 0.95). However, after left IIA AE, left IIV flow reduced by 54% ± 27% ( p < 0.01). Internal iliac artery AE had no effect on the external iliac arterial or venous flow rates and no effect on inferior vena cava flow rate. CONCLUSION: The effect of unilateral and bilateral IIA AE on IIV flow appears to be additive. Despite bilateral IIA AE, pelvic venous flow is diminished but not absent. There is abundant collateral circulation between the external and internal iliac vascular systems. Arterial embolization may reduce venous flow and improve on resuscitation efforts in those with unstable pelvic fractures. LEVEL OF EVIDENCE: Prognostic, level IV. Abstract : Supplemental digital content is available in the text.